Associations between pain, self-efficacy, sleep duration, and symptoms of depression in adolescents: a cross-sectional survey - Kristin Haraldstad; Tonje Holte Stea (BMC, 2021)
Abstract Background Although pain has been identified as an important public health problem among adolescents, few studies have investigated possible protective and risk factors for pain. The main aim of the present study was to investigate associations between prevalence of daily pain, self-efficacy, sleep duration, and symptoms of depression in a representative sample of Norwegian adolescents. Methods A comprehensive cross-sectional survey was completed by 12,867 junior high school students and high school students (response rate: 90%) aged 14-19 years. Logistic regression models were adjusted for age, gender, and parental educational level. Results We found a high prevalence of daily pain among adolescents, especially among girls (19%) compared with boys (7%). Short sleep duration was associated with increased odds ratios (ORs) of pain in the shoulders/neck (OR 1.3; 95% CI 1.3-2.0) and stomach (1.7; 1.2-2.4). Symptoms of depression were associated with increased ORs for all measured types of daily pain, including head (3.7; 3.0-4.6), shoulders/neck (3.9; 3.1-4.8), joints/muscles (4.3; 3.3-5.6), and stomach (5.5; 4.1-7.4). By contrast, self-efficacy was not associated with any form of daily pain. Conclusion Given the burden of pain, high incidence of pain problems, and strong association between pain and depression and, to some degree, short sleep duration, co-occurring symptoms may be an important area for research in the public health field. The results highlight the importance of early identification and prevention. Longitudinal studies are needed to understand better pain problems and their underlying mechanisms with the aim of developing targeted interventions.